Organ Donation and Transplantation: Psychological and Behavioral Factors. 1992
DOI: 10.1037/10134-004
|View full text |Cite
|
Sign up to set email alerts
|

Death attitudes and humor: Taking a different perspective on organ donation.

Abstract: organ donation has come about somewhat indirectly. Initially our aim was to investigate coping responses to stress within the domain of death attitudes and to explore the relation between cognitions, affect, and behaviors that arise in deathsalient contexts. For example, based on results of an initial pilot study (Shepherd, 1988), we have hypothesized that higher levels of mood disturbance experienced in death-related situations are associated with a negative evaluation of death and with the avoidance of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…In particular, the combination of fear and humor can increase the persuasive effects of arguments relating to health issues [25]. In terms of willingness to donate organs, there are some promising initial empirical findings demonstrating that a humorous tone is more effective than a sad one when motivating individuals to donate [26,27]. However, as yet, humor has rarely been used as a communication tool for health-related issues [28,29].…”
Section: Humor In Health Communicationmentioning
confidence: 99%
“…In particular, the combination of fear and humor can increase the persuasive effects of arguments relating to health issues [25]. In terms of willingness to donate organs, there are some promising initial empirical findings demonstrating that a humorous tone is more effective than a sad one when motivating individuals to donate [26,27]. However, as yet, humor has rarely been used as a communication tool for health-related issues [28,29].…”
Section: Humor In Health Communicationmentioning
confidence: 99%
“…[1][2][3][4][5] Research has shown that humor reduces stress, [6][7] enhances the immune system, [8][9][10][11][12] and has a positive effect on the cardiovascular system, the respiratory system, and the aging process. [13][14][15][16] Nursing research has focused on humor in a variety of healthcare settings including emergency rooms, 17 critical care units, 18 oncology settings, [19][20][21] geriatrics, 22 organ donation, 23 psychiatric wards, 24,25 rehabilitation facilities, 26 gynecology clinics, 27 and hospital wards. 1,28 It has also been examined in relation to death and dying.…”
Section: Introductionmentioning
confidence: 99%
“…Estudo 3 O objetivo deste estudo foi dar destaque a duas importantes variáveis que surgiram, tanto no decorrer dos dois estudos anteriores (principalmente no primeiro), quanto na revisão da literatura científica especializada: as relações existentes entre medo da morte, religião e doação de órgãos. Na literatura, tanto o medo da morte (Kopfman & Smith, 1996;Shepherd & Lefcourt, 1992;, quanto os aspectos religiosos (Kent & Owens, 1995;Radecki & Jaccard, 1997;Riether & Mahler, 1995), estão associados à não doação de órgãos. O Estudo 1, embora tenha sido conduzido numa perspectiva qualitativa, também sugeriu a possibilidade de conexões entre o medo da morte e a opção pela doação de órgãos (doador ou não doador).…”
Section: Resultsunclassified
“…Além da percepção do corpo, também se levou em conta que a maneira como a morte é tratada nos dias de hoje, em nossa cultura ocidental, pode funcionar como um potencial fator a influenciar a predisposição das pessoas relativamente à doação (favorável ou não favorável a ela). Estudos têm demonstrado que, quanto maior o medo da morte, maior parece ser a recusa pela doação de órgãos (Kopfman & Smith, 1996;Shepherd & Lefcourt, 1992;. Ocorre que a doação de órgãos pode funcionar como um tipo de imagem negativa da morte: ela pode evocar esta última ou então pode potencializá-la , sobretudo quando parece estar ligada à mutilação do corpo após a morte, ou seja, à retirada de um órgão exatamente num momento dolorido para a família que perdeu, por exemplo, um ente querido (René, Vieira, Daniels & Santos, 1994).…”
unclassified